Déjà Vu: The Untenable Reality of the Pavement Dwellers of Dhaka - Evidence from Three Decades - Anwara Begum; Kazi Zubair Hossain (Journal of Regional and City Planning, 2023)
Pavement dwellers migrate to the city in search of better opportunities. Their commitment to this way of life is based on an expectation of benefits in the destination area. This study examined five aspects of pavement dwellers’ reality: demographics, socioeconomics, migration outcomes, living conditions, and fulfillment of expectations. A mixed-method data collection exercise resulted in 64 pavement dwellers’ accounts of their current situation in Dhaka city, which were compared to similar studies from 1991 and 1993. The results show that their conditions have remained unchanged. Though half of the migration occurred for economic reasons, the real income level has remained the same as in 1991. Shelter and employment remain elusive, and moving to slums is financially infeasible. More than half of those interviewed lived on the pavement for access to a livelihood. Most declared that they could not access social safety nets. The persistence of pavement dwelling in the face of remarkable economic growth demands the refocusing of policies on urban poverty eradication.